2018
DOI: 10.1111/jocs.13558
|View full text |Cite
|
Sign up to set email alerts
|

Acute type A aortic dissection repair in younger patients

Abstract: Surgical outcomes after AAAD repair for young patients were satisfactory. A patent false lumen significantly increased the need for reoperation (P = 0.002), but did not affect long-term survival. Close follow-up is mandatory after the initial repair in young patients following AAAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Controversial results on the durability of aortic repair have been reported in a few studies evaluating young patients with TAAD. Among 51 TAAD patients younger than 50 years old, Uehara et al 3 reported distal aortic reoperations in 25% of patients after total aortic arch repair and in 17% of patients after hemiarch repair. However, 27.5% of their patients had a connective tissue disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversial results on the durability of aortic repair have been reported in a few studies evaluating young patients with TAAD. Among 51 TAAD patients younger than 50 years old, Uehara et al 3 reported distal aortic reoperations in 25% of patients after total aortic arch repair and in 17% of patients after hemiarch repair. However, 27.5% of their patients had a connective tissue disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Such an extensive surgical approach, often associated with completion endovascular treatment 2 , is thought to reduce the risk of distal progression of the disease by favouring the remodelling of the dissected downstream aorta and thus preventing aortic wall degeneration. This extensive surgical approach is attractive in young patients to reduce the incidence of distal aortic complications during their long lifespan 3 . However, data on the efficacy of total aortic arch repair in young patients are scarce 3–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Heuts et al 36 carried out a meta‐regression analysis which revealed that the treatment effect of TAR was potentialized with decreasing age, implying that the treatment effect of the more aggressive approach on 10‐year survival modestly increases with decreasing age. While younger patients have a longer life expectancy, they also have an increased risk of late distal aortic events and, eventually, require late reoperation more often, 39 which might justify a more aggressive approach initially to avoid reoperation (and its risks). Furthermore, younger age has been associated with more favorable peri‐operative results in the setting of ATAAD treated with the aggressive approach 26 .…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the proportion of hypertension, the incidence of AAAD has been increasing year by year. At present, timely surgical treatment is the main effective method for AAAD, but the early mortality after AAAD is still as high as 8–25% [ 3 , 4 ]. Therefore, early identification of risk factors for death on admission in AAD patients is of great significance to reduce mortality and improve prognosis.…”
Section: Introductionmentioning
confidence: 99%